Implementation of the Public Policy Strategy Model in Elementary School Education - Muhammad Al Mighwar; Desyana Nurlatipah (STIT Attaqwa, 2023)
This study aims to observe and describe various phenomena that arise during the implementation of the strategic model of basic education public policy. Using a qualitative descriptive approach, this research analyzes the supporting factors and inhibiting factors in the implementation of basic education, and it is found that teachers need to know more about the factors that support and hinder the implementation of education policies in elementary schools, principals, teachers, service education and society A joint effort is needed to implement it so that it can be provided to meet the appropriate needs of regular students and children with special needs to improve the quality and potential of primary school education services.